Selection of criteria in pedestrian wind comfort assessment - Gnatowska, Renata (Budownictwo i Architektura / Civil and Architectural Engineering, 2011)
Wind comfort in an built-up areas may be affected by a wide range of parameters, including wind speed, air temperature, relative humidity, solar radiation, air quality, human activity, age, etc. In practice, the assessment of the pedestrian comfort is carried out on the basis of the indexes defined to a considerably smaller number of parameters. Generally it is a criterion of wind velocity with the probability of exceeding the assumed discomfort threshold. This article discusses issues of spatial planning built-up areas including wind comfort criteria. The article pointed out the role of criteria adopted in estimation of discomfort areas. An important role is played here the value of the amplitude of the gust factor g. The attention was also drawn to the strong time variability of discomfort zones especially in areas close to buildings.